Congenital nasal pyriform aperture stenosis; our experience of 34 cases. (March 2023) - Chakravarty, Patrick Daragh; Sim, Fiona; Slim, Mohd Afiq Mohd; Patel, Neil; Wynne, David M.; Clement, William Andrew
Abstract: Objectives: To study our population of patients with congenital nasal pyriform aperture stenosis (CNPAS) in terms of incidence and socioeconomic status; the effect of pyriform aperture size, gestational age, birth weight, and whether congenital abnormalities are associated with surgical requirement. Methodology: Retrospective case note review of all patients treated for CNPAS at a single tertiary paediatric referral site was undertaken. Diagnosis was made on the basis of a pyriform aperture of <11 mm on CT scanning; patient demographics were collected to explore risk factors for surgery and surgical outcomes. Results: 34 patients were included in the series, 28 (84%) of whom underwent surgery. 58.8% of subjects had an associated mega central incisor. A smaller pyriform aperture size was seen in neonates requiring surgery (4.87 mm ± 1.24 mm vs 6.55 mm ± 1.41 mm, p = 0.031). There was no difference in gestational age in neonates requiring surgery (p = 0.074). Requirement for surgery was not associated with co-existing congenital anomalies (p = 0.297) or lower birth weight (p = 0.859). Low socioeconomic status was not significantly associated with requiring surgery but a potential link between CNPAS and deprivation was identified (p = 0.0583). Conclusion: These results suggest that a pyriform aperture of less than 6 mm requires surgical intervention. Associated birth anomalies add additional management considerations but in this cohort were not associated with increased need for surgery. A potential association between CNPAS and low socioeconomic status was identified.